Public Sector Facilities Maintenance and Organizational Efficiency: Evidence from InfraNodus-Based Analysis in Local Government - Nur Rini Abdullah; Gita Susanti; Muh Tang Abdullah (Department of Government Studies, Universitas Muhammadiyah Buton., 2025)
This study aims to examine the management of office facilities maintenance and its role in improving organizational performance efficiency in the Makassar City Public Works Department. The study adopts a qualitative descriptive approach to explore maintenance management practices within a local government context. Data were collected through observation, in-depth interviews, and documentation analysis, and further analyzed using qualitative content analysis and InfraNodus-based keyword network mapping. The findings indicate that maintenance management remains predominantly operational and reactive, with strong reliance on corrective actions rather than preventive strategies. Results show that maintenance practices are largely driven by public service demands and urban operational pressures, while strategic dimensions such as capacity building, performance competence, and systematic planning receive limited attention. The study highlights a structural gap between maintenance practices and organizational performance frameworks. Findings suggest that integrating maintenance management into strategic planning and adopting data-driven approaches are essential to enhance efficiency. Practically, this means that local government institutions need to strengthen preventive maintenance systems, improve coordination mechanisms, and utilize digital tools for monitoring and planning. This study is among the first to apply keyword network analysis to examine maintenance management discourse in a local government context, offering a novel perspective on linking maintenance practices with organizational performance efficiency.